The European Journal of Engineering Education as a venue for engineering education research publication: a meta view - Neto, Pedro (2017)
Trabalho apresentado 45th SEFI Conference, 18-21 September 2017, Angra do Heroísmo,Terceira Island, Azores, Portugal